2020
DOI: 10.3892/ijmm.2020.4572
|View full text |Cite
|
Sign up to set email alerts
|

EOFAZ inhibits endothelial‑to‑mesenchymal transition through downregulation of KLF4

Abstract: Essential oil from Alpinia zerumbet rhizome (EOFAZ), which is termed Yan shanjiang in china, is extensively used as an herbal medicine in the Guizhou area and has been shown to protect against the damaging effects of cardiovascular injury in vitro and in vivo. In the present study, it was hypothesized that the protective effects of EOFAZ on transforming growth factor (TGF)-β1-induced endothelial-to-mesenchymal transition (EndMT) in human umbilical vein endothelial cells (HUVEcs) were mediated by inhibition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…33 Although KLF4 is known to interact with TGF-β signaling to regulate endothelial-to-mesenchymal transition, it remains elusive whether and how KLF4 regulates the BMP/TGF-β signaling axes in ECs under health and disease conditions remain elusive. 35–38…”
mentioning
confidence: 99%
“…33 Although KLF4 is known to interact with TGF-β signaling to regulate endothelial-to-mesenchymal transition, it remains elusive whether and how KLF4 regulates the BMP/TGF-β signaling axes in ECs under health and disease conditions remain elusive. 35–38…”
mentioning
confidence: 99%
“…This study analyzed the expression of the CAV-1 gene in fibrotic muscles of rats submitted to treatment with the VOAz. An in vitro study observed that the use of the VOAz inhibited the extension of EndMT induced by TGF-β1 (Zhang et al, 2020). A negative involvement of the TGF-β1 has been reported in L-type calcium channels in cardiac muscles and in fibrotic cardiac pathology (Lei et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has suggested that eNOS/NO signaling axis was involved in vessel relaxation, vascular smooth muscle cell proliferation and ischemia/reperfusion injury ( 25 ). Moreover, our previous study revealed that KLF4 knockdown in endothelial cells could inhibit TGF-β-induced cell proliferation, migration and phenotypic changes, and effectively inhibited EndMT, suggesting that KLF4 may serve a role in EndMT ( 26 ). However, to the best of our knowledge, few studies have investigated the regulatory effect of the KLF4/eNOS signaling pathway in vascular damage-associated disorders.…”
Section: Discussionmentioning
confidence: 99%